Adsorption of Atoms on Thymine: Density Functional Theory - Ahmad Zabidi, Noriza; Nazrul Rosli, Ahmad; Abu Kassim, Hasan; K.N, Shrivastava; P.V, Rao; V.R, Devi (Malaysian Journal of Science, 2007)
We calculate the adsorption energy of F, Cl, Br, I, At, H, Li, Na, K, Rb, Cs, and Fr on the thymine molecule. The calculation is performed by using the quantum mechanical density functional theory. The calculation has been performed in the local density approximation (LDA), in the generalized gradient approximation with exchange (GGA-X) as well as in the generalized gradient approximation with exchange and correlations (GGA-XC). We are able to find the adsorption energy as well as its variation as a function of atomic number of the adsorbed atom.